A study for substance culture - Ertekin, Gülsüm; Çakmak, Duran (Journal of Dependence, 2001)
In this study, the relationship between substance and its addicts, subculture of substance addiction, life style and route of substance using were elucidated by a group of substance addicts. The patients diagnosed as substance addicts in the AMATEM Clinic, Detoxification department between the dates December 1995-January 1996 took part in this study. Focus group study technique was used to collect information. In this study, we interviewed 42 patients-3 women-39 men-who were distributed to 5 to 7 membered groups. Interviews lasted 9 sessions. We interviewed about the substances taken-the routes of taking-the names they give among themselves-the place and the kind of music they prefer while taking substance-the methods they use while heroin withdrawal and in the state of intoxication-from whom and where they buy the substances-substances which are difficult to find -substances which are out of market and new released drugs were determined. As a result, we have achieved information about “substance culture” in this study. It is determined that there are similarities between the information we got and other researchers had found. However, there is need for further studies.
Keywords: substance culture; substance use; addiction